2023
DOI: 10.18494/sam4141
|View full text |Cite
|
Sign up to set email alerts
|

Optical and Scintillation Characteristics of Tb-doped La2Si2O7 Single Crystal

Abstract: Lanthanum pyrosilicate La 2 Si 2 O 7 (LaPS) single crystals were successfully fabricated by the floating zone (FZ) method with Tb doping concentrations of 0.1, 0.5, 1.0, and 2.0% for scintillation and photoluminescence (PL) study. X-ray diffraction patterns of the samples indicate a single phase of LaPS from their consistency with the reference pattern. Tb-doped LaPS has multiple emissions from Tb 3+ 4f-4f transitions including those at 380, 420, 440, 480, 540, 590, and 620 nm, as observed in both PL and X-ray… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…The obtained lifetimes of Tb-doped crystals resulted in 1.8-2.3 ms, and the results were typical values for the 4f-4f transitions of Tb 3+ ions. [35][36][37] In addition, 0.1% and 0.5% Tb-doped crystals have slower rise times. This phenomenon can be due to the cross-relaxation between the neighboring Tb 3+ ions.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…The obtained lifetimes of Tb-doped crystals resulted in 1.8-2.3 ms, and the results were typical values for the 4f-4f transitions of Tb 3+ ions. [35][36][37] In addition, 0.1% and 0.5% Tb-doped crystals have slower rise times. This phenomenon can be due to the cross-relaxation between the neighboring Tb 3+ ions.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Such an event would be blamed for the main origin of IRF. The main decay component of both Lumilass-G9 and R7 was 1.3 ms, and this value was typical for scintillation of Tb 3+ - 67,68) and Eu 3+ -doped 69,70) phosphors. Scintillation decay times became faster than PL ones, which suggested that some quenching phenomena occurred during the energy transportation process.…”
Section: Optical Propertiesmentioning
confidence: 74%
“…Single crystalline scintillators have been extensively investigated [15][16][17][18][19][20] owing to their high optical properties and high homogeneity. For instance, the following crystals are representatively implemented in practice: Bi 4 Ge 3 O 12 (BGO), [21][22][23][24] CdWO 4 (CWO), [25][26][27] and Tl-doped NaI and CsI.…”
Section: Introductionmentioning
confidence: 99%